2012
DOI: 10.1007/978-1-4471-2852-6
|View full text |Cite
|
Sign up to set email alerts
|

Distributed-Order Dynamic Systems

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. While the advice and information in this book are believed to be true and accurate at the date of publication, neither the authors nor the editors nor the publisher can accept any legal responsibility for any errors or omissions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(37 citation statements)
references
References 0 publications
0
36
0
1
Order By: Relevance
“…In this paper, we use the following definition of distributed-order differential/integral operators [8]:…”
Section: Solution Of Distributed-order Differential Equations On Non-mentioning
confidence: 99%
“…In this paper, we use the following definition of distributed-order differential/integral operators [8]:…”
Section: Solution Of Distributed-order Differential Equations On Non-mentioning
confidence: 99%
“…But, in recent decades, this has changed. It was found that fractional calculus is useful, even powerful, for modelling viscoelasticity [4], electromagnetic waves [5], boundary layer effects in ducts [6], quantum evolution of complex systems [7], distributed-order dynamical systems [8] and others. That is, the fractional differential systems are more suitable to describe physical phenomena that have memory and genetic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Materials whose constitutive equations can be described by a fractional derivative [5] are of increasing interest in recent years (see [30,29]). It is well known that materials with such properties can be considered in the class of materials with memory and may describe elastic, fluid and electromagnetic materials, but also other kinds of phenomena, such as heat flux models.…”
Section: Introductionmentioning
confidence: 99%
“…The creep function for such models also has power law form. Such experimental backing has motivated many studies of materials with fading memory given by a fractional derivative, including [6,22,4,14,17,30,23] and in the frequency domain [19,36]. Many experimental observations on a variety of materials subject to a constant load show plastic behavior, which can be described by the fractional derivative approach.…”
Section: Introductionmentioning
confidence: 99%